2014
DOI: 10.1007/s12562-014-0767-1
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory observations on the vertical swimming behavior of Japanese common squid Todarodes pacificus paralarvae as they ascend into warm surface waters

Abstract: This study examined the effect of warm temperature on the survival of paralarvae of Japanese common squid Todarodes pacificus and on their swimming behavior as they ascended to the surface. Observations were conducted on paralarvae in Petri dishes and in 85-cm-tall, cylindrical tanks that had a warmer upper layer and cooler lower layer separated by a small thermocline. Paralarvae were obtained through artificial fertilization and reared in Petri dishes at six experimental temperatures between 20.9 and 30.4°C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Given that squid paralarvae of D . gigas and Todarodes pacificus are demonstrably sensitive to temperature gradients [ Camarillo‐Coop et al ., ; Staaf et al ., ; Yoo et al ., ], and possibly also to dissolved oxygen [ Gilly et al ., ] , net haul sampling was carried out in these three layers. For the purposes of the cruise, the thermocline was defined as the temperature band 16–22°C, which was roughly centered around the maximum temperature gradient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that squid paralarvae of D . gigas and Todarodes pacificus are demonstrably sensitive to temperature gradients [ Camarillo‐Coop et al ., ; Staaf et al ., ; Yoo et al ., ], and possibly also to dissolved oxygen [ Gilly et al ., ] , net haul sampling was carried out in these three layers. For the purposes of the cruise, the thermocline was defined as the temperature band 16–22°C, which was roughly centered around the maximum temperature gradient.…”
Section: Methodsmentioning
confidence: 99%
“…Vertical distributions of fish larvae are often separable into strata associated with the surface mixing layer, thermocline/chlorophyll a maximum layer, and deeper layers [e.g., Danell-Jim enez et al, 2009;Davies et al, 2015]. Given that squid paralarvae of D. gigas and Todarodes pacificus are demonstrably sensitive to temperature gradients [Camarillo-Coop et al, 2011;Staaf et al, 2011;Yoo et al, 2014], and possibly also to dissolved oxygen , net haul sampling was carried out in these three layers. For the purposes of the cruise, the thermocline was defined as the temperature band 16-228C, which was roughly centered around the maximum temperature gradient.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…A longer developmental time within the egg mass also provides an enhanced opportunity for developing embryos to absorb organic nutrients from the oviducal gland jelly (Bower and Sakurai, 1996). Vertical swimming experiments conducted by Yoo et al (2014) with T. pacificus revealed that the paralarvae consistently have a preference for surface layers. Field surveys also collected hatchling-sized paralarvae at the surface waters (Yamamoto et al, 2002).…”
Section: Paralarval Recruitmentmentioning
confidence: 96%
“…In fact, transport by currents has been shown to be a powerful dispersal mechanism for planktonic squid [9–14] and octopus paralarvae [15, 16]. In addition to this passive transport, the swimming capacities recorded in the laboratory for planktonic cephalopod hatchlings are within the range or higher than those found for the larval fishes [1722], which could enhance their dispersal potential. In contrast, mark and recapture experiments with hatchlings of large, benthic cuttlefish, showed limited shallow water dispersal, as the individuals remain in the same or adjacent bays to those in which they hatched [23].…”
Section: Introductionmentioning
confidence: 99%